PCDH7 as the key gene related to the co-occurrence of sarcopenia and osteoporosis - Liu, Mingchong; Wang, Yongheng; Shi, Wentao; Yang, Chensong; Wang, Qidong; Chen, Jingyao; Li, Jun; Chen, Bingdi; Sun, Guixin (Frontiers in Genetics, 2023)
Sarcopenia and osteoporosis as two of the most common degenerative diseases in older patients have become severe health problems in the aging society. Muscles and bones as the most important part of the motor system are derived from mesodermal and ectodermal mesenchymal stem cells, and the adjacent anatomical relationship between them provides the basic conditions for mechanical and chemical signals, which may contribute to the co-occurrence of sarcopenia and osteoporosis. Identifying the potential common crosstalk genes between sarcopenia and osteoporosis may provide new sight for preventing and treating their development. In this study, DEGs analysis, WGCNA, and machine learning algorithms were used to identify the key crosstalk genes of sarcopenia and osteoporosis, then validations were performed by using independent datasets and clinical samples. Finally, four crosstalk genes (ARHGEF10, PCDH7, CST6, and ROBO3) were identified, and mRNA expression and protein levels of PCDH7 in clinical samples from patients with sarcopenia, with osteoporosis, with both sarcopenia and osteoporosis, were significantly higher than those from patients without sarcopenia or osteoporosis. PCDH7 was a key gene related to the development of both sarcopenia and osteoporosis.